Ein Konzept zur Regionalisierung des Klimas komplexer Mittelgebirgslandschaften, veranschaulicht am Beispiel des Osterzgebirges - Goldberg, Valeri; Bernhofer, Christian (ERDKUNDE, 2000)
This study presents a concept of regionalization, that aims at a physically based and spatially detailed description of the regional climate. Its application is demonstrated for the Eastern Ore Mountains. The regional and local climate was characterized by empirical relationships between the climatological quantity (e.g., temperature and precipitation) and height above sea level. The small-scale effects of geometry (slope and aspect) and surface characteristics on climate are quantified by model approaches to parameterize radiation, temperature and precipitation in complex terrain. The theoretically generated results are mainly presented in nomograms and they are suitable for direct practical use (e.g., radiation for solar energy applications). These regionalization algorithms are transferred into a digital elevation model. This yields highly resolved areal information of important climatological standard values and extreme values of radiation, temperature and precipitation depending on topography and landuse. Especially the spatial distribution of extreme values cannot be derived from routine data. But it is of great interest for potential users of climatic data (e.g., in forestry). Exemplary results in a test area in the upper region of the Eastern Ore Mountains show that the modelled daytime temperature maximum on March 21 differs in a wide range of 43 K and the hydrological summer precipitation varies between upwind and downwind slopes in a range of 31 %. This concept of regionalization can be transferred to other mountain areas if the topography and the landuse are known and the large-scale climatic conditions are similar to the investigated area. The combination of empirical and modelled data leads relatively fast to new climate information and valuable results for various applications in environmental planning.